2003
DOI: 10.2337/diacare.26.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Concomitants of Glucose Intolerance in European Obese Children and Adolescents

Abstract: OBJECTIVE -The worldwide increase in the prevalence of childhood obesity is reaching epidemic proportions and is associated with a dramatic rise in cases of type 2 diabetes. The prevalence of glucose intolerance and its determinants and the relation of cardiovascular risk factors with levels of glycemia and degree of obesity were studied in grossly obese children of European origin. RESEARCH DESIGN AND METHODS-A total of 710 grossly obese Italian children (SD score [SDS] of BMI 3.8 Ϯ 0.7) aged 6 -18 years, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
116
5
10

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(149 citation statements)
references
References 42 publications
18
116
5
10
Order By: Relevance
“…15,35 If CRP levels are Metabolic syndrome and nontraditional CVD risk factors in obese children C Invitti et al obesity-driven, MS might fail to influence CRP in the context of an all obesity cohort. This paper has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,35 If CRP levels are Metabolic syndrome and nontraditional CVD risk factors in obese children C Invitti et al obesity-driven, MS might fail to influence CRP in the context of an all obesity cohort. This paper has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…14 The adult definition is unlikely to apply to children in that, as we have previously shown, HOMA-IR changes during childhood depending on the pubertal stage. 15 We have considered HOMA-IR values greater than the median value for each of the Tanner stages as an indicator of insulin resistance. This corresponded to values of 2.4, 2.8, 3.0, 4.1 and 3.0, respectively, for stages I, II, III, IV and V.…”
Section: Definitionsmentioning
confidence: 99%
“…11 In children and adolescents, however, although severe obesity plays a prominent pathogenetic role in type 2 diabetes, whether it is a risk factor for IGT in this population, remains unclear. Several recent studies demonstrated that IGT too has become a major concern in obese children and adolescents, 12,13 but information on the factors that contribute to this clinical problem is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…O grau de ganho de peso durante a infância e adolescência está diretamente relacionado aos níveis de fatores de risco cardiovasculares em adultos jovens. A obesidade em crianças e adolescentes parece estar relacionada ao aumento de DCV independente da resistência insulínica (7). Atualmente existem provas definidas de que as crianças com maiores índices de massa corporal (IMC) terão, já na adolescência, níveis mais elevados de pressão arterial, triglicerídeos, colesterol total, glicemia em jejum e insulina (8).…”
Section: Introductionunclassified